2023
DOI: 10.29000/rumelide.1342264
|View full text |Cite
|
Sign up to set email alerts
|

Ein neuer Ansatz zur Fehleranalyse: Eine explorative Fallstudie zu den häufigsten schriftlichen Kompetenzfehlern im L3-Deutschen

Abstract: Diese Studie zielte darauf ab, die häufigsten schriftlichen Kompetenzfehler zu ermitteln, die von Senior-StudentInnen der Abteilung für Fremdenführung, deren L1 Türkisch und L2 Englisch war, beim Schreiben eines argumentativen Essays im L3-Deutschen gemacht wurden. Außerdem wurden die Quellen und Ursachen ihrer schriftlichen Kompetenzfehler dafür untersucht. Es ist seit langem bekannt, dass zahlreiche Faktoren den Prozess des Spracherwerbs und -lernens beeinflussen und dass eine systematische Fehleranalyse Leh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…One could argue that they made this pronoun error because they directly transferred features from the English language to the German language. This finding is consistent with study of Tanır (2023b). In this study, it was revealed that students learning German as a third language made morphological mistakes.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 92%
“…One could argue that they made this pronoun error because they directly transferred features from the English language to the German language. This finding is consistent with study of Tanır (2023b). In this study, it was revealed that students learning German as a third language made morphological mistakes.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 92%